Benzene and Methane Adsorption on Ultrahigh Surface Area Carbons Prepared from Sulphonated Styrene Divinylbenzene Resin by KOH Activation - Jerzy Choma; Łukasz Osuchowski; Aleksandra Dziura; Michal Marszewski; Mietek Jaroniec (Adsorption Science & Technology)
A commercially available styrene divinylbenzene ion-exchange resin, Amberjet 1200 H, was used to prepare a series of activated carbons through carbonization and subsequent activation with varying amounts of KOH. The resulting activated carbons showed a well-developed porous structure with specific surface area in the range of 730–3870 m 2 g −1 , total pore volume in the range of 0.44–2.07 cm 3 g −1 and micropore volume in the range of 0.30–1.59 cm 3 g −1 . Importantly, these structural parameters can be changed by varying the amount of KOH used for the activation. These carbons showed extremely good adsorption properties towards benzene and methane at 20°C. The best uptakes for benzene and methane (19.6 and 1.68 mmol g −1 , respectively) were obtained for the carbon activated using the KOH/C ratio of 4. These values correspond to the gravimetric adsorptions of 1.53 g/g and 27 mg/g, respectively. Benzene adsorption was analyzed using the Dubinin–Radushkevich (DR) equation. The micropore volume calculated using the DR equation based on benzene adsorption corresponds well with the micropore volume calculated from nitrogen adsorption by the α s comparative method. The high values of the structural parameters and the resulting high benzene and methane uptakes render the obtained activated carbons as prospective materials for use in environmental remediation and energy-related applications such as volatile organic compound adsorption and methane storage.